2017
DOI: 10.14295/transportes.v25i2.1046
|View full text |Cite
|
Sign up to set email alerts
|

Análise crítica e ajuste de modelos de previsão de fadiga com análise incremental de danos para BGTC executada em pavimento asfáltico semirrígido

Abstract: O dano que gera fadiga em camadas cimentadas é função dos diferentes esforços que solicitam a estrutura. Este conceito é o princípio da análise de dano acumulado, cujo uma das formas mais utilizadas de contabilização é pela Lei de Miner. Contudo, com o avanço progressivo do dano, a rigidez das camadas do pavimento é reduzida. Baseando-se nesses conceitos, realizou-se um estudo neste trabalho para avaliação de cinco modelos de previsão de desempenho para ruptura por fadiga em camada de Base de Brita Graduada Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the technical-scientific literature on the subject, it is observed that research has analyzed the sensitivity of flexible pavements dimensioned by MEPDG in view of the effects of the variation of surface course thickness, base and subbase on the development of fatigue cracks [11,12]. Other studies evaluated performance prediction models for fatigue rupture in cement treated gravel base layer (BGTC) [13]. However, it is identified the absence of studies that analyze the implications, on the dimensioning of asphalt pavements, resulting from the adoption of different fatigue models and the consideration of the possible additional influence of geometric variables (thickness), mechanics (engineering properties of structural materials) and loading (axle load) in the mechanistic-empirical protocol.…”
Section: Introductionmentioning
confidence: 99%
“…In the technical-scientific literature on the subject, it is observed that research has analyzed the sensitivity of flexible pavements dimensioned by MEPDG in view of the effects of the variation of surface course thickness, base and subbase on the development of fatigue cracks [11,12]. Other studies evaluated performance prediction models for fatigue rupture in cement treated gravel base layer (BGTC) [13]. However, it is identified the absence of studies that analyze the implications, on the dimensioning of asphalt pavements, resulting from the adoption of different fatigue models and the consideration of the possible additional influence of geometric variables (thickness), mechanics (engineering properties of structural materials) and loading (axle load) in the mechanistic-empirical protocol.…”
Section: Introductionmentioning
confidence: 99%